A relação com o outro como forma de enfrentamento à experiência do câncer infantil em sistema nervoso central: significados de pacientes, mães e profissionais para a jornada do tratamento - Nars, Clarissa Carvalho Fongaro [UNIFESP] (2019)
Because it is a chronic condition, cancer requires complex care, being Central Nervous System tumors in childhood, one of the diseases that imposes more challenges to its coping, by the transformations generated in the body. Although it is a rare disease, cure rates have been increasing and, while thinking about Humanization practices in Health, bringing up for discussion what those involved in the process have to say about this experience becomes of utmost importance. Thus, in this research, we intend to understand the meanings attributed to the experience of having the life marked by childhood cancer in Central Nervous System, through the intertwining of narratives of those involved with this treatment at the end of the experience. And, from this general objective, we intend to understand also possible coping mechanisms to the referred experience. For this, it was designed a qualitative research, in which we chose the use of the Oral History of Life methodology. Nine collaborators were interviewed at a Paediatric Oncology unit in the city of São Paulo, including patients aged seven to thirteen, their mothers and professionals. Subsequently, the narratives were interpreted in the light of Borkan's immersion/ crystallization approach, based on the style of Hermeneutic Phenomenology. The narratives were interpreted using Jacqueline Lagrée’ Philosophy. With the intertwining of the narratives, it was possible to find a central theme that emerged from the narratives of all the collaborators: the relationship with the other as a way of coping with the experience of childhood cancer in the Central Nervous System. This relationship was understood through theoretical assumptions that the patient is considered a person, who is constructed from the relation with the other and from singular experiences. Dialogue is how these relationships are established. The ways of relating that emerged as sub-themes and gave meaning to the experience for all the collaborators were: the professional-patient relationship, the professional-family relationship, the support relationships of the family, the friendship relations and the technical knowledge as the mediating discourse of such relationships. This permeates all the narratives and is also configured as a way to signify the experience. Although the primacy of this discourse is emphasized, the emphasis given by the collaborators to the human aspect during treatment makes us consider that, in addition to the undisputed importance of the medical protocol for the success of the treatment, the relationship with the other has been configured as a crucial resource in the scope of healing. Thus, the dialogical relationship with the other meets a proposal that considers the human during cancer treatment, contributing to the discussions about Humanization in Health, which may favor the development of strategies for the complex care of childhood cancer.